Flash heating of epoxy based corrosion inhibitor thin films on aluminum substrates - Muhammad, Ban Walid (Journal of natural sciences, life and applied sciences, 2022)
The following investigation shows the experimental evaluation of a transient heat load centered on a corrosion inhibitor coating employed in the epoxy polyamide primary. The temperature at which the epoxy polyamide film initiated thermal deterioration increased with increased heating rates. This coating is a Deft Inc.’s high- quality solid epoxy primary. A single inch diameter lamp on two types of aluminum substrates was focused on the xenon flashlight: AA2024- T4 and AA7075- T3. For modeling purposes, edge effects have not been explored. The ceramic firebrick isolated the coated aluminum disks to ensure minimum edge effects. The FTCS model has been designed to calculate the temporary reaction to the thermal energy flash load. It has been demonstrated that substrates have a substantial impact on epoxy polyamide film energy absorption, film surface temperatures and absorbed energy.